In Silico Antibacterial Activity of Polyacetilene Derivatives Against Mycobacterium tuberculosis and In-Vitro Antioxidant Properties from Ethanol Extraction of Blackjack (Bidens pilosa L.) - Firman Wicaksana; Fadila Sofi; Mohammad Rafly (Jurnal Kimia Sains dan Aplikasi, 2024)
Blackjack (Bidens pilosa L.) has a bioactive compound, one of which is polyacetylene, which can inhibit the growth of antimicrobials in general. This study aims to conduct an in silico study to determine the antibacterial activity against Mycobacterium Tuberculosis of 20 derivatives polyacetylene; TPC was determined by Folin–Ciocalteu colorimetric method using gallic acid as standard, and various concentrations of the extract solutions were measured at 741 nm. TFC was calculated using an aluminum chloride colorimetric assay. Quercetin was used as standard, and the absorbance was measured at 426 nm. Antioxidant activity was evaluated using DPPH scavenging 517 nm and Frap Assay 596 nm. The molecular docking results showed that the compounds (5-(2-Phenylethynyl)-2-b-glucosylmethyl-thiophene, Glucopyranosyloxy-3-hydroxy-6(E)-tetradecane-8,10,12-triyne and Phenylhexa-1,3,5-triyn-1-yl acetate were most potentially anti-tuberculosis on the target protein InhA with the binding energy produced <-6.55 Kcal/mol and the lowest inhibitory cost of 1.838×10-6. The compound has amino acids similar to natural ligands and standard compounds of isoniazid. The given ADME-T predictions showed good pharmacokinetic properties and safe levels of toxicity (5-(2-Phenylethynyl)-2-b-glucosylmethyl-thiophene, Glucopyranosyloxy-3-hydroxy-6(E)-tetradecane-8,10,12-triyne in hepatotoxic and LD50. The highest antioxidant properties in blackjack are produced by FRAP assay 722.905±7.985 mMTE/gr. This proves that blackjack has antioxidant activity and is required for bioassay-guided isolation testing against Mycobacterium tuberculosis.